Increasing the Tolerance of DCD Hearts to Warm Ischemia by Pharmacological Postconditioning. Issue 8 (8th July 2014) - Iyer, A.; Gao, L.; Doyle, A.; Rao, P.; Jayewardene, D.; Wan, B.; Kumarasinghe, G.; Jabbour, A.; Hicks, M.; Jansz, P. C.; Feneley, M. P.; Harvey, R. P.; et al.
<x xml:space="preserve">Abstract</x> Donation after circulatory death (DCD) offers a potential additional source of cardiac allografts. We used a porcine asphyxia model to evaluate viability of DCD hearts subjected to warm ischemic times (WIT) of 20–40 min prior to flushing with Celsior (C) solution. We then assessed potential benefits of supplementing C with erythropoietin, glyceryl trinitrate and zoniporide (Cs), a combination that we have shown previously to activate ischemic postconditioning pathways. Hearts flushed with C/Cs were assessed for functional, biochemical and metabolic recovery on an ex vivo working heart apparatus. Hearts exposed to 20‐min WIT showed full recovery of functional and metabolic profiles compared with control hearts (no WIT). Hearts subjected to 30‐ or 40‐min WIT prior to C solution showed partial and no recovery, respectively. Hearts exposed to 30‐min WIT and Cs solution displayed complete recovery, while hearts exposed to 40‐min WIT and Cs solution demonstrated partial recovery. We conclude that DCD hearts flushed with C solution demonstrate complete recovery up to 20‐min WIT after which there is rapid loss of viability. Cs extends the limit of WIT tolerability to 30 min. DCD hearts with ≤30‐min WIT may be suitable for transplantation and warrant assessment in a transplant model.